Tingkat Pengetahuan dan Pelaksanaan Pap Smear Pada Ibu Pasangan Usia Subur di Dusun Kemasan Desa Karang Tengah Imogiri Bantul Tahun 2015 - Khotimah, Chusnul; Noviawati Setya Arum, Dyah; Hernayanti, Munica Rita (Jurnal Kesehatan Ibu dan Anak, 2017)
Cervical cancer is the second most common cancer in the world. In developing countries still ranks first as a cause of cancer deaths in women of reproductive age. Pap smear has proved very useful for early detection of cervical cancer since pre-cancerous stage, but many women are reluctant to undergo a pap smear because of ignorance, shame, fear, and cost factors. While the Pap smear coverage lowest in Imogiri health center II is 0%. The type of research is a descriptive study with cross-sectional approach. To describe the level of knowledge and overview of the implementation of Pap smears in women in fertile age couple in the Kemasan Hamlet Karang Tengah Village Imogiri Bantul. The entire population of mothers in fertile age couple who attended of the PKK and willing to become respondents in the Kemasan Hamlet Karang Tengah Village Imogiri Bantul. The results of research that the majority of respondents aged> 35 years (51.1%), basic education (50%), does not work (53.44%), obtain resources through one source (63.3%). The level of knowledge about Pap smears in women PUS (Pasangan Usia Subur) in the Kemasan Hamlet Karang Tengah Village Imogiri Bantul 2015 is in the category enough that 72.7% and most did not carry out pap smear that is, 86.4%. The conclusion that the level of knowledge about the EFA mother pap smear EFA in the Kemasan Hamlet Karang Tengah Village Imogiri Bantul 2015 enough and did not carry out pap smear.